Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00417-009-1038-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contrast sensitivity, depth of field and ocular wavefront aberrations in eyes with an IOL with zero versus positive spherical aberration

Abstract: Eyes with the SofPort Advance Optics neutral aberration IOL demonstrated less spherical aberration and better low-contrast acuity compared to eyes with a spherical IOL, without sacrificing tolerance to defocus. The aspheric IOL showed superior optical and clinical performance, which is most likely due to its surface design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
(72 reference statements)
0
5
2
1
Order By: Relevance
“…It was anticipated that the Crystalens AO group would have better contrast sensitivity compared with the multifocal IOL groups 1,3,21. However, in this study the Crystalens AO group only had significantly better contrast sensitivity at lower spatial frequencies.…”
Section: Discussioncontrasting
confidence: 54%
“…It was anticipated that the Crystalens AO group would have better contrast sensitivity compared with the multifocal IOL groups 1,3,21. However, in this study the Crystalens AO group only had significantly better contrast sensitivity at lower spatial frequencies.…”
Section: Discussioncontrasting
confidence: 54%
“…This measured value of 0.14 D for mean depth of focus is accurate and in accordance with reports in the literature. 14,15,18,29 Rocha et al 33 found a positive correlation between ocular spherical aberration and depth of focus in a clinical study that was the first to evaluate the potential effects of aberrations on objective depth of focus, with no correlations found between 3rd-order aberrations (trefoil and coma) and objective depth of focus. However, Oshika et al 17 showed that corneal aberrations might influence apparent accommodation.…”
Section: Discussionmentioning
confidence: 96%
“…13 Although Marcos et al 14 showed the potential impact of negative aspheric IOLs on reducing depth of field, other studies 9,15 found that the increased Strehl ratio obtained with neutral aspheric IOLs did not adversely affect depth of field. These varying results may be accounted for by residual spherical aberrations interacting with whole-eye aberrations.…”
mentioning
confidence: 97%
“…We must keep in mind that interaction between residual SA with other higher and lower wavefront errors is not completely understood, particularly with neural adaptation. More attention to the full spectrum of corneal higher order aberrations using an optical adaptative device, biometry, IOL specifications, IOL decentration and tilt, and pupil size would be important to realise a nomogram for the preoperative selection of aspheric IOLs 3 14 23…”
Section: Discussionmentioning
confidence: 99%